Measuring the Mental Health-Care System Responsiveness: Results of an Outpatient Survey in Tehran - Forouzan, Setareh; Padyab, Mojgan; Rafiey, Hassan; Ghazinour, Mehdi; Dejman, Masoumeh; San Sebastian, Miguel (Frontiers in Public Health, 2016)
Abstract As explained by the World Health Organisation (WHO) in 2000, the concept of health system responsiveness is one of the core goals of health systems. Since 2000, further efforts have been made to measure health system responsiveness and the factors affecting responsiveness, yet few studies have applied responsiveness concepts to the evaluation of mental health systems. The present study aims to measure responsiveness and its related domains in the mental health care system of Tehran. Utilising the same method used by the WHO for its responsiveness survey, responsiveness for outpatient mental health care was evaluated using a validated Farsi questionnaire. A sample of 500 public mental health service users in Tehran participated and subsequently completed the questionnaire. On average, 47% of participants reported experiencing poor responsiveness. Among responsiveness domains, confidentiality and dignity were the best performing factors while autonomy, access to care and quality of basic amenities were the worst performing. Respondents who reported their social status as low were more likely to experience poor responsiveness overall. Autonomy, quality of basic amenities and clear communication were responsiveness dimensions that performed poorly but were considered to be important by study participants. In summary, the study suggests that measuring responsiveness could provide guidance for further development of mental health care systems to become more patient orientated and provide patients with more respect.